EVALUASI KINERJA SEISMIK STRUKTUR BAJA DENGAN METODE PUSHOVER ANALYSIS: (Studi Kasus Gedung Fakultas Keguruan dan Ilmu Pendidikan Universitas Siliwangi Kota Tasikmalaya) - Siti Salma, Andani Raudah; Defiana, Yanti; Saepudin, Uu (Jurnal Ilmiah Teknik Sipil, 2025)
Indonesia is located in a high seismic activity region, which poses significant risks of structural damage and casualties. One of the important educational facilities is the Faculty of Teacher Training and Education (FKIP) building at Universitas Siliwangi, Tasikmalaya, which is constructed using a steel structural system. This study aims to evaluate the seismic performance of the building based on FEMA 356 guidelines through pushover analysis using SAP2000 v22.2.0 software. The analysis focuses on target displacement, plastic hinge distribution, and structural performance levels categorized as Immediate Occupancy (IO), Life Safety (LS), and Collapse Prevention (CP). The results indicate that the building achieved the IO performance level in both directions. The maximum base shear reached 12228.46 kN in the X-direction and 7435.65 kN in the Y-direction, with maximum displacements of 268.66 mm and 269.50 mm, respectively. Plastic hinges were mainly formed in beam elements but remained within the Immediate Occupancy (IO) limit without triggering structural failure. Therefore, the FKIP building meets the seismic safety criteria in accordance with FEMA 356 and is considered adequate to function as an educational facility.